Comparative analysis of Sentinel-1 InSAR ground motion data dissemination strategies: towards an optimal model for Serbia - M. Basarić (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2025)
Ground Motion Services (GMS), based on Interferometric Synthetic Aperture Radar (InSAR) technology, are key components in monitoring terrain deformation and managing geohazards. European countries have developed various national GMS platforms that differ significantly in their data dissemination approaches, including access models, update frequency, visualization tools, and integration with national geospatial infrastructures. This paper presents a comparative analysis of online accessible open GMS platforms of Norway, Sweden, Germany, the Netherlands, Romania, and Hungary alongside the European Ground Motion Service (EGMS). The focus is placed on identifying strengths and limitations in current dissemination practices, with the aim of determining optimal strategies for user accessibility, data transparency, and interoperability. Based on the findings, the paper proposes a conceptual model for a future Serbian GMS (SrbGMS), grounded in principles of open access, standardized visualization, and harmonization with European frameworks. The results contribute to a better understanding of best practices in InSAR-based data dissemination, supporting the development of more effective and inclusive ground motion monitoring services. Special emphasis is placed on alignment with the INSPIRE Directive, as the foundational premise of this research is that the future SrbGMS should be fully compatible with the INSPIRE framework. The study establishes the optimal criteria for the evaluation of dissemination platforms and presents a comparative assessment of existing services.